The Role of the Namora Natoras Mandailing Traditional Institutions in Forced Marriage in Affairs Cases - Nasution, Muhammad Idris; Adly, Muhammad Amar; Nurcahaya, Nurcahaya (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2022)
Forced marriage has no legitimacy in Indonesian marriage law, and is instead categorized as a crime of sexual violence. However, these forms of forced marriage are still common, especially in the case of adultery, as happened in Mandailing, and gain legitimacy from its customary institutions. The purpose of this article is to describe how the role and perception of Namora Natoras in forcing an adulterer's marriage to the principle of consent of the bride and groom. This juridical-empirical research was conducted by collecting data through interviews and other secondary data. The data was processed qualitatively by using content analysis. The results show that Namora Natoras plays an effective role as a customary justice institution in cases of forced marriage in adultery cases, in order to fill the legal vacuum. In Namora Natoras' perception, forcing an adulterer to marry an adulteress is a customary sanction, as an effort to find a balance of nature and provide a deterrent effect, preventing children from being born out of wedlock, a form of repentance, and a form of protection for women to avoid worse perceptions from society. Namora Natoras is of the view that forcing adulterers to marry is more beneficial than upholding the principle of consent of the bride and groom in this case in order to protect the rights of women and children